El modelo transteórico del comportamiento en salud (2000)
ABSTRACT: The transtheoretical model of health behavior change is a product of a comparative analysis of leading theories of psychotherapy and behavior change. The model uses a temporal dimension, the stages of change, to integrate processes and principles of change from different theories, hence the name transtheoretical. Posits that of health behavior change involves progress through five stages of change: precontemplation, contemplation, preparation, action, maintenance and termination. Another core constructs of the transtheoretical model are processes of change, decisional balance, self-efficacy and temptation. This article presents the origins and core components of model and the way to use his constructs in research and practice in the context of health promotion based models.